Dynamic Changes at Yahtse Glacier, the Most Rapidly Advancing Tidewater Glacier in Alaska - Durkin, William J.; Bartholomaus, Timothy C.; Willis, Michael J.; Pritchard, Matthew E. (Frontiers in Earth Science, 2017)
Since 1990, Yahtse Glacier in southern Alaska has advanced at an average rate of ∼100 m/yr despite of a negative mass balance, widespread thinning in its accumulation area, and a low accumulation-area ratio. To better understand the interannual and seasonal changes at Yahtse and the processes driving these changes, we construct velocity and ice surface elevation time series spanning the years 1985-2014 and 2000-2014, respectively, using satellite optical and synthetic aperture radar (SAR) observations. In terms of seasonal changes, we find contrasting dynamics above and below a steep (up to 18% slope) icefall located approximately 6 km from the terminus. Above the icefall, speeds peak in May and reach minima in October synchronous with the development of a calving embayment at the terminus. This may be caused by an efficient, channelized subglacial drainage system that focuses subglacial discharge into a plume, resulting in a local increase in calving and submarine melting. However, velocities near the terminus are fastest in the winter, following terminus retreat, possibly off of a terminal moraine resulting in decreased backstress. Between 1996-2014 the terminus decelerated by ∼40% at an average rate of ∼0.4 m/day/yr , transitioned from tensile to compressive longitudinal strain rates, and dynamically thickened at rates of 1-6 m/yr , which we hypothesize is in response to the development and advance of a terminal moraine. The described interannual changes decay significantly upstream of the icefall, indicating that the icefall may inhibit the upstream transmission of stress perturbations. We suggest that diminished stress transmission across the icefall could allow Yahtse’s upper basin to remain in a state of mass drawdown despite of moraine-enabled terminus advance. Our work highlights the importance of glacier geometry in controlling tidewater glacier re-advance, particularly in a climate favoring increasing equilibrium line altitudes.